Why 1D electrical resistivity techniques can result in inaccurate siting of boreholes in hard rock aquifers and why electrical resistivity tomography must be preferred: the example of Benin, West Africa - (:unkn) unknown (My University, 2018)
Hard rock aquifers are of particular importance for supplying people with drinking water in Africa and in the world. Although the common use of one-dimensional (1D) electrical resistivity techniques to locate drilling site, the failure rate of boreholes is usually high. For instance, about 40% of boreholes drilled in hard rock aquifers in Benin are unsuccessful. This study investigates why the current use of 1D techniques (e.g. electrical profiling and electrical sounding) can result in inaccurate siting of boreholes, and checks the interest and the limitations of the use of two-dimensional (2D) Electrical Resistivity Tomography (ERT). Geophysical numerical modeling and comprehensive 1D and 2D resistivity surveys were carried out in hard rock aquifers in Benin. The experiments carried out at 7 sites located in different hard rock groups confirmed the results of the numerical modeling: the current use of 1D techniques can frequently leads to inaccurate siting, and ERT better reveals hydrogeological targets such as thick weathered zone (e.g. stratiform fractured layer and preferential weathering associated with subvertical fractured zone). Moreover, a cost analysis demonstrates that the use of ERT can save money at the scale of a drilling programme if ERT improves the success rate by only 5% as compared to the success rate obtained with 1D techniques. Finally, this study demonstrates, using the example of Benin, that the use of electrical resistivity profiling and sounding for siting boreholes in weathered hard rocks of western Africa should be discarded and replaced by the use of ERT technique, more efficient.
Keywords: African Research